Challenges In Translation of Proverbs - Achilov Oybek Rustamovich (Genius Journals, 2024)
This article shows that proverbs and sayings, examples of folklore are distinguished from each other by their national characteristics and uniqueness, and specific difficulties arise during the translation process based on these cultural characteristics, and the translator should translate them in a manner specific to the culture of the nation
Keywords: cultural nuances; idiomatic expressions; wordplay and puns